Kombinasi Jumputan Dengan Teknik Manipulasi Tekstil Shirring - Khansa Zahra Kinasih; Li Hsun Peng (Corak, 2025)
The tie-dye technique is one of the techniques for making textile pattern that has long been used in Indonesia. Jumputan is one of the traditional fabrics made using the tie-dye technique. The process of making jumputan, which uses tie and sewing techniques, creates wrinkles. The resulting wrinkles are combined with shirring textile manipulation techniques with the aim of adding a new aesthetic to jumputan while making a slim impression on certain parts. The design method used as a way to solve the problem is SP Gustami's theory. The stages carried out in solving the problem are exploration, design and realization. The combination of jumputan and shirring technique was made into women's clothing. The resulting work is in the form of clothes with motifs made using jumputan technique combining shirring textile manipulation technique. The combination of shirring technique can add the function of jumputan wrinkle.ABSTRAKTeknik ikat celup merupakan salah satu teknik pembuatan motif tekstil yang sudah lama digunakan di Indonesia. Jumputan merupakan salah satu kain tradisional yang dibuat menggunakan teknik ikat celup. Proses pembuatan jumputan yang menggunakan teknik ikat serta menjahit, menciptakan sebuah kerutan. Kerutan yang dihasilkan dikombinasi dengan teknik tekstil shirring dengan tujuan untuk menambahkan estetika baru pada jumputan sekaligus membuat kesan ramping pada bagian tertentu. Metode perancangan yang digunakan sebagai cara penyelesaian masalah adalah teori SP Gustami. Tahap yang dilakukan dalam penyelesaian masalah yaitu tahap eksplorasi, perancangan dan perbaikan. Kombinasi jumputan dan teknik shirring dibuat menjadi pakaian wanita. Karya yang dihasilkan berupa pakaian dengan motif yang dibuat menggunakan teknik jumputan mengkombinasikan teknik manipulasi tekstil shirring. Kombinasi teknik shirring dapat menambahkan fungsi dari kerut jumputan